Contribuciones hermenéuticas para tratar con la diversidad desde la lingüisticidad de la comprensión - Gende, Carlos Emilio (Pontificia Universidad Católica del Perú, 2021)
The observation of linguistic diversity is frequently used as a datum to explain cultural diversity. In this way, two types of experiences, very different in their mode of constitution, are homologized, making it impossible to derive valuable consequences that would help us understand them. We aim to, first of all, review the assumptions of this theoretical attitude, which describes language as a product, and then to present some features of Ricoeur's position, which assumes it as a process oriented towards understanding.

Es habitual emplear la constatación de la diversidad lingüística, como dato, para explicar la diversidad cultural. Así, se homologan dos tipos de experiencias muy distintas en su modo de constitución, impidiendo con ello extraer consecuencias valiosas para entenderlas. Nos proponemos, en primer término, revisar los supuestos de esa actitud teórica, que describe al lenguaje como producto, para luego presentar algunos rasgos de la posición de Ricoeur, que lo asume como proceso orientado a la comprensión.
Hermeneutic contributions to deal with diversity from linguistics of understanding
Keywords: Diversity; Language; Culture; Diversidad; Lenguaje; Cultura